Psychological well-being focusing on anxiety and depression among patients with lower urinary tract symptoms in benign prostatic hyperplasia on pharmacological treatment in HUSM - Tanapalla, Sejjeetra Raynee (2020)
Introduction : Lower urinary tract symptoms (LUTS) in Benign Prostatic Hyperplasia (BPH) have a negative impact on the quality of life, and may relate to anxiety and depression. The aim of the present study was to investigate the prevalence of anxiety and depression among patients with LUTS/BPH as well as to determine their correlation. Methodology : A cross-sectional study was conducted from July 2019 to October 2019 among 153 patients who had been diagnosed with LUTS/BPH under the Surgical Clinic Hospital Universiti Sains Malaysia follow up, by using a set of self-administered questionnaires which includes sociodemographic profile, the Malay version of the International Prostate Symptoms Score (IPSS) and the Malay version of Hospital Anxiety and Depression Scale (HADS). Data was analyzed using measure of frequency for prevalence of anxiety and depression in LUTS/BPH and correlation analysis to study the relationship between them. Results : The study reported 27.5% prevalence of depression and 15.0% anxiety among patients with LUTS/BPH. The study results also indicated that there was positive correlation between severity of depression (r=0.426, p-value <0.001) and anxiety (r=0.367, p-value <0.001) with severity of LUTS/BPH. Conclusion : Depression and anxiety are significantly prevalent among patients with LUTS/BPH. There is also positive correlation between severity of depression and anxiety with LUTS/BPH. Comorbidity of these conditions should draw the attention of both psychiatrists and urologists as well as enhance the interdisciplinary treatment approach. Further prospective and cohort studies are essential to reveal more details of the correlation between LUTS and anxiety/depression.